Metabolic profile is not associated with body composition parameters in recreational female futsal players: Metabolic profile and recreational female futsal players - Campos, Eduardo Zapaterra [UNESP]; Gerosa-Neto, José [UNESP]; Lira, Fábio Santos [UNESP]; Buonani, Camila [UNESP] (Springer Nature, 2016)
Objective: To investigate the association between body composition parameters and the metabolic profile of recreational female futsal players. Methods: 11 recreational female futsal players (21.2 ± 1.4 years, 163.2 ± 4.0 cm and 61.3 ± 17.6 kg) participated in this study. The assessment of body composition was performed using Dual Energy X-ray Absorptiometry, and the following body composition variables were evaluated: total body mass (TBM); body mass index (BMI); total body fat; relative total body fat; upper body fat (UBF); relative upper body fat (RUBF); lean mass (LM); lower limb muscle mass (LLMM). In addition, an evaluation of the metabolic profile was conducted: triacylgrycerol (TAG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c) and plasma concentrations of glucose (Glu). For the statistical analysis, descriptive analysis and the Pearson test were used to verify association between metabolic profile and body composition. The significance level was 5 %. Results: No significant association was found between TAG, HDL-c, and TC/HDL-c to body composition variables, while LDL-c had a tendency to associate with TBM (r = 0.54; p = 0.08) as well as Glu to BMI (r = −0.56; p = 0.07), and TBM (r = −0.59; p = 0.05). Significant association was found between Glu and LM (r = −0.73; p < 0.01) and TC with LLMM (r = 0.59; p = 0.055). Conclusion: No significant association was found between the metabolic profile and body fat indices, which may be explained by the relatively low levels of TAG, TC, and LDL-c.
Keywords: LDL-c; Lean mass, fat mass; Total cholesterol